In vitro effects of photodynamic therapy induced by chloroaluminum phthalocyanine nanoemulsion - Franchi, Leonardo Pereira; Amantino, Camila F.; Melo, Maryanne T.; de Lima Montaldi, Ana Paula; Primo, Fernando L. [UNESP]; Tedesco, Antonio Claudio (Elsevier, 2016)
Background The photodynamic therapy (PDT) has been used to treat cancer mainly by inducing oxidative stress. Our aim was to evaluate the effect of PDT and its combination with methoxyamine (MX), a blocker of base excision repair (BER), in cells expressing high levels of the APE1 protein, which is involved in cell oxidative damage response. Methods The HeLa and A549 cells were treated for 3 h with chloroaluminum phthalocyanine incorporated into a well-designed nanoemulsion (ClAlPc/NE); and then irradiated by visible light (@670 nm) with doses of 0.1, 0.5 and 1.0 J/cm2. A simultaneous combination of MX + ClAlPc/NE was performed and then irradiated with the selected dose of 0.5 J/cm2. The treatments were evaluated in terms of viability, clonogenicity, DNA fragmentation, and cell death mechanism by apoptosis and/or necrosis. Results The APE1 protein expression observed was higher in HeLa than in A549. Both cell lines exhibited substantial differences in cell cytotoxicity. The PDT decreased the clonogenicity of HeLa by inducing apoptosis (sub-G1 and annexin detection). Additionaly, the MX potentiates the PDT-effects in HeLa. Otherwise, low cytotoxicity was observed in A549 cells. Conclusion The PDT induced apoptosis in high APE1 expressive HeLa cells, and the blockage of BER by MX increased its effects.
Keywords: Cancer cell lines; Chloroaluminum phthalocyanine; Cytotoxicity; DNA repair; Flow cytometry